Mycobacterial growth inhibition in murine splenocytes as a surrogate for protection against Mycobacterium tuberculosis (M. tb) - Marsay, L; Matsumiya, M; Tanner, R; Poyntz, H; Griffiths, K; Stylianou, E; Marsh, P; Williams, A; Sharpe, S; Fletcher, H; McShane, H (2013)
Development of an improved vaccine against tuberculosis (TB) is hindered by the lack of a surrogate of protection. Efficacy of new TB vaccines in humans can only be evaluated by expensive and time consuming efficacy trials within TB endemic areas. It is critical that vaccines with the greatest potential to protect are selected for these trials. Mycobacterial growth inhibition assays (MGIAs) have been developed with the hope that these in-vitro functional assays will correlate with protection, which could aid in the selection of the best vaccine candidates. The present study describes the use of the BACTEC system to perform MGIAs in mice. We demonstrate reproducible mycobacterial growth inhibition in splenocytes from BCG immunised mice compared with unimmunised mice (P < 0.023), which corresponded with in-vivo efficacy against Mycobacterium tuberculosis (M. tb) challenge. Microarray data showed extensive differential gene expression in splenocyte responses to ex-vivo BCG stimulation between unimmunised and BCG-immunised mice. TH1 responses, including IFN-γ, nitric oxide synthase (NOS2) and Interleukin -17 (IL-17) expression were enhanced in BCG immunised mice, indicating a possible mechanism for mycobacterial growth inhibition. Further investigation into whether the BACTEC MGIA can be used as a surrogate of protection in humans and preclinical animal models is now warranted. © 2013 Published by Elsevier Ltd.